Readiness to Implement Project-Based Learning: The Influence of Knowledge and Attitude among Community College Lecturers - Ealangov, Suganti; Jamaludin, Khairul Azhar (Journal of Technical Education and Training, 2024)
Implementing project-based learning (PjBL) at Community Colleges can result in highly competent and competitive students. However, due to a lack of research, the level of readiness among Community College lecturers to apply PjBL remains an issue. As a result, the aim of this study is to establish the level of readiness among Community College lecturers in terms of knowledge, attitudes, and skills to implement PjBL. This study also seeks to ascertain the influence of knowledge and attitude factors on Community College lecturers' ability to execute PjBL. This study was carried out using a quantitative approach and a survey design. Data was collected using a questionnaire. The study sample included 400 Community College lecturers who were chosen using a stratified convenience sampling approach. Descriptive analysis was used to examine the mean scores of knowledges, attitude, and skills in implementing PjBL, while inference analysis using multiple regression tests was used to determine the contribution of knowledge and attitude variables to PjBL implementation skills. Both analyses were carried out using the SPSS Statistics for Windows 26.0 programme. The findings show that Community College lecturers are highly prepared to apply PjBL. Overall, the knowledge and attitude variables contributed 64.1% to the skills in applying PjBL, with the knowledge factor having a larger effect than the attitude factor. The findings have an impact on lecturers in terms of preparedness and aid management in understanding the factors that influence lecturers' readiness. This understanding is crucial for planning and delivering appropriate support services to lecturers in their professional development.